Management of Intergenerational Conflict in the Workplace and Its Impact on Employee Relations - Wardani, Febri Pramudya; Krismayanti, Yanti; Sacha, Shinta; Siahaan, Rahel Sintadevi; Anjarsari, Nisa; Rumambi, Freddy Johanis (PT FORMOSA CENDEKIA GLOBAL, 2024)
Intergenerational conflict in the workplace stems from differences in values, work preferences, communication styles, and adaptability to technology among Baby Boomers, Generation X, Millennials, and Generation Z. This qualitative descriptive study examines the forms, impacts, and management strategies of such conflicts. Findings reveal that these conflicts manifest in communication mismatches, work-life balance expectations, and varying technological adaptability, leading to interpersonal tension, reduced productivity, and fragmented workplace dynamics. Effective management through open communication, intergenerational training, and collaborative projects can transform conflicts into opportunities for innovation and synergy. The study highlights practical recommendations for managers and HR professionals and contributes to theoretical discussions on managing generational diversity. Future research should quantitatively explore the link between generational conflict and organizational performance.